Evaluating MXene-doped PEDOT coating on carbon fiber microelectrodes for dual-functional neural interfacing - Sorel E. De León; Rana Jaylani; Young Jun Jung; Negin Jalilinejad; Toon Goris; Simon Higham; Kate Fox; Michael Ibbotson; Steven Prawer; Shadi Houshyar; Wei Tong; David J. Garrett (Analytica Chimica Acta, 2026)

The Genomic Signature of Demographic Decline in a Long‐Distance Migrant in a Range‐Extreme Population - George Day; Thomas Bolderstone; Greg J. Conway; Tony Cross; Tony Davis; Matilda Dolan; Mervyn Greening; Colin Neale; Ian Nicholson; Kim Nicholson; Ann Ward; Nik Ward; et al. (Molecular Ecology, 2025)
Migratory birds are inherently vagile, a strategy that may reduce the impacts of habitat loss and fragmentation on genetic diversity. However, specialist resource requirements and range‐edge distribution can counteract these benefits. The European nightjar ( Caprimulgus europaeus ) is a long‐distance migratory bird and resource specialist. Like other long‐distance migrants, nightjar populations have declined across the British Isles and Northwestern Europe over the past century. With this decline well documented in the British Isles, there is a need to quantify its genetic impacts. We applied full genome resequencing to 60 historic (1841–1980) and 36 contemporary British nightjars. Nightjars exhibited a statistically significant 34.8% loss in heterozygosity and an increase in inbreeding over the last ~180 years, showing a departure from panmixia towards weak spatial structure in the modern population. Such fine‐scale structuring in migratory birds is rare. Our results provide a case study of fragmentation's impact on a species with specialist resource requirements at its range limit. Similar demographic declines in nightjars and other long‐distance migrants across Northern and Western Europe suggest that genetic patterns seen in the British population may reflect those in other nightjar populations and European avifauna. Whilst our results indicate no immediate conservation concern, they depict a trajectory of declining genetic diversity, increasing inbreeding and genetic structure, potentially shared with other migratory species. Our study highlights the value of applying spatiotemporal population genetics analysis to migratory birds, despite their inherent vagility.

Pandemic gardening: A narrative review, vignettes and implications for future research - Jonathan Kingsley; Kelly Donati; Jill Litt; Naomi Shimpo; Chris Blythe; Jan Vávra; Silvio Caputo; Paul Milbourne; Lucy O. Diekmann; Nick Rose; Runrid Fox-Kämper; Agnes van den Berg; et al. (Urban Forestry & Urban Greening, 2023)

Biological Abundance and Diversity in Organic-Rich Sediments From a Florida Barrier Island Lagoon - Kate M. Fuller; Austin L. Fox; Charles A. Jacoby; John H. Trefry (Frontiers in Marine Science, 2021)
Organic-rich sediments in estuaries and the coastal ocean are often a product of land clearing, runoff of excess nutrients and other human activities. They can harbor pollutants, oxygen-consuming microbes and toxic hydrogen sulfide (H 2 S), thereby creating a hostile environment for infauna. In one barrier island lagoon, the Indian River Lagoon (IRL), Florida, layers of organic-rich sediments have increased substantially in thickness and areal extent over the past 60 years. Geochemical properties of these muddy sediments have been described; however, less is known about their habitability. We analyzed infauna and geochemical properties of 102 samples taken during wet and dry seasons at 17 locations spanning 60 km of the lagoon. We quantified infaunal abundance and diversity (Shannon-Wiener, H′) and determined Pearson’s correlation coefficients for effective number of species (ENS = e H ′) vs. sediment porosity (ϕ = 0.69–0.95), organic carbon (1–8%), nitrogen (0.1–0.7%), silt + clay (16–99%), porewater H 2 S (5–3,600 μM), and other environmental variables. Small bivalves accounted for 70% of the organisms collected, followed by gastropods, polychaetes and other biota. The bivalves were predominantly Macoma spp., Mulinia lateralis and Parastarte triquetra with average abundances of 3,896, 2,049, and 926 individuals per m 2 , respectively. High abundance of some species, such as Macoma , showed that these opportunists had adapted to poor quality sediments. More than two-thirds of the 35 species collected were present at <100 individuals per m 2 of sediment. Cluster analysis identified four groups of stations with significantly different geochemical properties. Permutation analyses of variance indicated that the four groups also represented statistically different infaunal communities. Diversity decreased with increasing sediment concentrations of organic carbon, nitrogen and silt + clay; however, community richness at our most prolific station along the perimeter of muddy deposits was ∼7 times lower than found previously in sandy sediments from the IRL. The results identified areas where infaunal communities have experienced the greatest stress due to accumulation of organic-rich sediments. Results from this study help support management plans for remediation of organic-rich mud and improvement of sediment and water quality, especially in areas identified with low ENS.

Automated Template-Based Hippocampal Segmentations from MRI: The Effects of 1.5T or 3T Field Strength on Accuracy - Kate E. Macdonald; Kelvin K. Leung; Jonathan W. Bartlett; Melanie Blair; Ian B. Malone; Josephine Barnes; Sebastien Ourselin; Nick C. Fox (Neuroinformatics, 2014)